Effect of Website-based Learning on Improved Monitoring of Adverse Drug Reactions by Clinical Nurses - Hyun jin Kim; Seon Young Hwang (Elsevier, 2022)
SUMMARY: Purpose: The purpose of this study was to develop website-based learning contents to activate voluntary monitoring and reporting of adverse drug reactions (ADRs) for clinical nurses and to verify their effectiveness. Method: Using a quasi-experimental control group pretest-posttest design with random allocation, a total of 60 nurses with more than 1 year of clinical experience were recruited from a university hospital in Seoul, Korea. A website was developed that provides learning contents including real cases and the latest drug-related knowledge, as well as video lectures. Knowledge on ADR monitoring, self-efficacy, ADR practice behavior, and medication performance ability were measured at 2 weeks after intervention. A small notebook for monitoring ADRs of nurses was given to the control group. Data were analyzed using descriptive statistics, the chi-squared test, and the independent t test using SPSS Statistics Software Version 21.0. Results: The scores of ADR monitoring knowledge, self-efficacy, and ADR monitoring practice in the experimental group significantly increased after the intervention compared with the control group (p < .05). However, there was no significant difference between the two groups in medication performance ability related to ADR monitoring. Conclusion: To spread a safety culture in which voluntary ADR monitoring and reporting is activated, it is necessary for clinical nurses to share and communicate ADR-related information and real cases through an open website.